If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-(8x+5)=15+2(11-7x)
We simplify the equation to the form, which is simple to understand
x-(8x+5)=15+2(11-7x)
Remove unnecessary parentheses
x-8x-5=15+2*(11-7x)
Reorder the terms in parentheses
x-8x-5=15+(+22-14x)
Remove unnecessary parentheses
+x-8x-5=+15+22-14x
We move all terms containing x to the left and all other terms to the right.
+1x-8x+14x=+15+22+5
We simplify left and right side of the equation.
+7x=+42
We divide both sides of the equation by 7 to get x.
x=6
| 3+2x=3(2x+4)-5(x-2) | | 3x-(8-x)=5(3-x)+4 | | -7+2x=-25-x | | x-(8-x)=5(3-x)+4 | | 10+12=-34+x | | 2x+10-7x=3(x-5)+1 | | 3*(x+2)=3x+32 | | 7(2x+1)=5x+16 | | 9x+8+2x+6=7x+2 | | 8x-5x=8 | | 10p-4=86 | | -7+8x-19=15+3(x-17) | | 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 | | x+8(12-x)=7x(5x-42) | | -8x-5x-96=60 | | 8/3=n/4 | | x-7x-61=23 | | 7=2[r+6]-5 | | r(x)=x(13-0.04x) | | -15=10+5v | | -2x-10+3x=9 | | 62=-7v-1 | | 2[w+2]=10 | | 9x^4/3x^3 | | 3a-1/6-1-4a/12=1 |